Brill's Encyclopedia of China (Brill, 2009)
Brill’s Encyclopedia of China Online is based on the originally a thousand-page reference work on China with a clear focus on the modern period from the mid-nineteenth century to the 21st century. Written by the world’s top scholars, Brill’s Encyclopedia of China is the first place to look for reliable information on the history, geography, society, economy, politics, science, and culture of China. (Cited description, Brill 2021)
Gesehen am 19.04.2011
Coverage 2009-
Keywords: searchable full text; Datenbank; China